KELAYAKAN MODUL MATERI SISTEM EKSKRESI KELAS VIII SMP - Rany Rahmadhania; Ruqiah Ganda Putri Panjaitan; Eko Sri Wahyuni (Universitas Tanjungpura, 2017)
AbstractThis research aims to know the feasibility of excretion system module for 8th grade junior high school. The research used descriptive method with survey form. Research instrument used is sheet validation. Feasibility assessment of the module is obtained through validity test by 5 examiners. Validity test including presentation aspect, gradability, content and language. The average value of each aspects are 3,78; 3,56; 3,63; and 3,6. From the result of module validation, the obtained average value is 3,64 which categorised as valid. It is concluded that the module is feasible to use as teaching material of excretion system for 8th grade junior high school.Keywords: Feasibility, Modul, Material Excretion System